Rancang Bangun Ulang Motor Listrik Berbasis Android Dengan Sistem Motor Brushless Direct Current (BLDC) 3 Phase Kapasitas 1000 Watt - Prasetyo, Yudha Mahendra; Budiarto, Sigit; Perdana, Mahendra Putra; Siswadi, Siswadi (Faculty of Engineering, Wijaya Putra University, 2022)
Electric vehicles use an electric motor as a driving force where it functions as a converter of electrical energy stored in the battery into mechanical energy to turn the wheels of the vehicle. Electric motors can reduce fuel consumption and air pollution produced by motorized vehicles, so electric vehicles are one of the transportation modes they can use. In this research, the design of a BrushLess Direct Current (BLDC) motor as a motorcycle propulsion was carried out. The BLDC motor has the main components, namely the stator and rotor. This electric motor designed uses a BLDC type E-BIKE with specifications for 1000 Watt power and an input voltage frequency of 60Hz, and a rotating speed of 500Rpm with a 3.75V-25Ah BMS battery in 16 series to 60V-25Ah. This E-BIKE type BLDC electric motorcycle model can be adapted to the shape of a motorcycle drum with a wheel diameter of 17 inches.